2013
DOI: 10.1007/s40368-013-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eruptive intracoronal dentine radiolucencies in the permanent dentition of Jordanian children

Abstract: PEIR defects occur at a significant prevalence rate in unerupted teeth. Increased awareness and careful radiographic examination of unerupted teeth may improve early detection and treatment of PEIR defects in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
51
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 13 publications
12
51
2
9
Order By: Relevance
“…In the present study, all the cases of intracoronal resorption were located just beneath the dentinoenamel junction, as reported in previous studies (Grundy et al, '84;Seow et al, '99a;Hata et al, 2007;€ Ozden and Acikgoz, 2009;Al-Batayneh et al, 2014;Uzun et al, 2015). Al-Batayneh et al (2014) reported that 50% of defects extended to less than one-third of the dentin thickness. This figure is comparable to that reported in other studies, which reported that 85% and 55% of defects were less than one-third of the dentin thickness, respectively (Seow et al, '99b;Noriah Nik and Abdul Rahman, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, all the cases of intracoronal resorption were located just beneath the dentinoenamel junction, as reported in previous studies (Grundy et al, '84;Seow et al, '99a;Hata et al, 2007;€ Ozden and Acikgoz, 2009;Al-Batayneh et al, 2014;Uzun et al, 2015). Al-Batayneh et al (2014) reported that 50% of defects extended to less than one-third of the dentin thickness. This figure is comparable to that reported in other studies, which reported that 85% and 55% of defects were less than one-third of the dentin thickness, respectively (Seow et al, '99b;Noriah Nik and Abdul Rahman, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…In the study by Al‐Batayneh et al . () all the subjects had only one affected tooth, pointing to a role for local etiologic factors. This finding is in accordance with that of other studies (Özden and Acikgoz, ; Uzun et al ., ), although some authors (Wood and Crozier, ; Seow et al ., ; Hata et al ., ) reported more than one affected tooth in the same individual.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations